Peningkatan Kemampuan Motorik Kasar Melalui Tari Kreasi Di TK Putri Kembar Pasir Julu - Laila Mupida Nasution; Mira Yanti Lubis; Silfa Hafizah Pulungan (Institut Nalanda, 2024)
Based on the results of research carried out by the author, it can be concluded that (1) Gross motor skills in the Kembar Pasir Julu Girls' Kindergarten are still low, namely in the Not Yet Developed (BB) category of 2 children or 11.76%, while the gross motor skills of children in the Starting to Develop (MB) category ) 8 children or 47.06%, the gross motor skills of children in the Developing According to Expectations (BSH) category were 6 children or 35.29%, while the gross motor skills of children in the Very Well Developing (BSB) category were 1 child or 5.88%. (2) Improving children's gross motor skills through the implementation of Kreasi Dance at the Kembar Pasir Julu Girls' Kindergarten in cycle I has started to increase, namely there are no children in the Not Yet Developed (BB) category, while the gross motor skills of children in the Starting to Develop (MB) category are 5 children or 29 .41%, the gross motor skills of children in the Developing According to Expectations (BSH) category were 8 children or 47.06%, while the gross motor skills of children in the Very Well Developing (BSB) category were 4 children or 23.53%. in cycle II it has increased, namely there are no children in the Not Yet Developing (BB) category, while the gross motor skills of children in the Starting to Develop (MB) category are 1 child or 5.88%, the gross motor skills of children in the Developing According to Expectations (BSH) category are 8 children or 47 .06%, while the gross motor skills of children in the Very Well Developed (BSB) category were 8 children or 47.06%. So it can be concluded that the implementation of creative dance at the Kembar Pasir Julu Girls' Kindergarten can improve children's gross motor skills.